2016
DOI: 10.1186/s40064-016-2894-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of β-sitosterol with antibacterial activity from the root bark of Malva parviflora

Abstract: The powder of root bark of Malva parviflora (Malvaceae) was successively extracted with petroleum ether (b.p. 60-80 °C), chloroform and ethanol. The chloroform extract showed antibacterial activity against Staphylococcus aureus and Escherichia coli, whereas the ethanolic extract showed antibacterial activity against only S. aureus. The chloroform extract, after column chromatographic separation on silica gel using petroleum ether:chloroform (3:1) as eluent, furnished 98 mg of white crystalline compound. The yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 13 publications
7
75
0
1
Order By: Relevance
“…On the basis of above discussion and combined NMR and mass data, the structure of compound 1 was established to be 2-bromodimethylbenzene-1,4-dioate. To the best of our knowledge, both compounds 1 and 2 have not been described earlier as natural products, while compound 2 has been synthesized previously by many researchers [31][32][33] The structures of the known compounds ( Figure 1) were determined as fucosterol (3) [34][35][36], nhexadecanoic acid, methyl ester (4) [37,38], ꞵ-sitosterol (5) [35,39], cerotic acid (6) [40,41], n-octacos-9enoic acid (7) [42,43], and 11-eicosenoic acid (8) [44,45], on the basis of their spectral data and the comparison of their spectral data with those reported in literature. Compound 2 was obtained as a colorless amorphous powder with the molecular formula C 12 H 13 BrO 4 , deduced from the HR-ESI-MS and 13 C-NMR data ( Figure 1).…”
Section: Structure Elucidation Of Compounds 1-8mentioning
confidence: 99%
“…On the basis of above discussion and combined NMR and mass data, the structure of compound 1 was established to be 2-bromodimethylbenzene-1,4-dioate. To the best of our knowledge, both compounds 1 and 2 have not been described earlier as natural products, while compound 2 has been synthesized previously by many researchers [31][32][33] The structures of the known compounds ( Figure 1) were determined as fucosterol (3) [34][35][36], nhexadecanoic acid, methyl ester (4) [37,38], ꞵ-sitosterol (5) [35,39], cerotic acid (6) [40,41], n-octacos-9enoic acid (7) [42,43], and 11-eicosenoic acid (8) [44,45], on the basis of their spectral data and the comparison of their spectral data with those reported in literature. Compound 2 was obtained as a colorless amorphous powder with the molecular formula C 12 H 13 BrO 4 , deduced from the HR-ESI-MS and 13 C-NMR data ( Figure 1).…”
Section: Structure Elucidation Of Compounds 1-8mentioning
confidence: 99%
“…Some important others such as β‐sitosterol and stigmasterol were lower than 10%. β‐Sitosterol has been shown to have antioxidant and anti‐inflammatory properties (Dighe, Kuchekar, & Wankhede, ; Manral et al, ; Ododo et al, ), and it is considered to play a role in the reduction of cholesterol. Antitumorigenic, antimetastatic, and significant anti‐inflammatory effects have been revealed as a result of application in in vitro studies (Dighe et al, ; Kraft, Freeling, Wang, & Ho, ; Rashed & Fouche, ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, only extracts of D. suffruticosa exhibited significant DNA damage in leukocytes ( Figure 4) as shown by a p value < .05 (Table 3). (Dighe, Kuchekar, & Wankhede, 2016;Manral et al, 2016;Ododo et al, 2016), and it is considered to play a role in the reduction of cholesterol. Antitumorigenic, antimetastatic, and significant anti-inflammatory effects have been revealed as a result of application in in vitro studies (Dighe et al, 2016;Kraft, Freeling, Wang, & Ho, 2014;Rashed & Fouche, 2013).…”
Section: Comet Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al (2010) Of note, at present no other study regarding the antibiotic modulatory effect of marine sponges has been reported, as well as, additional studies aimed at identifying the molecular mechanism underlying the antimicrobial property of this sponge extract remain to be carried out. isolated (Ododo et al 2016, Subramaniam et al 2014, Sanches et al 2005. Sponges of the genus Neopetrosia are still yielding novel bioactive molecules; neopetrocyclamines A and B (Liang et al, 2015), 9'-epi-3β, 3'β-dimethylxestospongin C (Li et al, 2011) and exiguamine A (Brastianos et al, 2006) and this was the impetus for the investigation of a member of this genus.…”
Section: Accepted Manuscriptmentioning
confidence: 99%